On time and meaningful partisanship: Stability, strength, and sway of attachment to new parties - Pannico, Roberto (2022)
New parties pose a challenge to the claim that time is an essential element in the construction of partisanship. By definition, new parties have not been around for much time, so the opportunities for the construction of meaningful attachments could be considered limited. In this paper, we test this expectation, unpacking the dynamics and implications of the attachment to new parties. Using panel data collected in Spain during a period of profound party system change, we estimate the extent to which partisanship with new parties is stable and strong, works as a heuristic for preference formation, and predicts vote choice. Our data suggest that attachments to new parties can be as meaningful as those that citizens have with old parties. These findings seem particularly relevant in a context where new parties are on the rise.